Anxiety treatment with herbal medicines - Rocha, Heloisa Costa Belmiro; Arakawa, Janice Aparecida Rafael (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Farmácia, 2022)
Anxiety is considered a more common mental disorder among people, there are some medicinal plants such as chamomile, melissa, passionflower, valerian, cava and lavender, which can have an effect of improving these anxiety symptoms in the individual's body. They are plants with a calming, sedative action, which act on the central nervous system causing the individual to improve the state of health. The present work refers to some medicinal plants that can promote an improvement for the individual who suffers from this disorder, and / or alleviating the symptoms. The study presents as descriptions of substances of the plants in question, as well as how it should be used.